2008
DOI: 10.3171/spi.2008.10.0831
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory cerebral adaptations before and evolving changes after surgical decompression in cervical spondylotic myelopathy

Abstract: Object The goal of this study was to compare cortical sensorimotor adaptations associated with neurological deterioration and then recovery following surgical decompression for cervical spondylotic myelopathy (CSM). Methods Eight patients with CSM underwent functional MR (fMR) imaging during wrist extension and the 3-finger pinch task, along with behavioral assessments before and 3 and 6 months after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
82
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 39 publications
(51 reference statements)
10
82
1
3
Order By: Relevance
“…In a larger study by Dong et al, 13 which included 8 patients with CSM and 6 healthy control volunteers, the authors quantitatively captured reduced activation in the contralateral M1, S1, and dorsal PMA for dexterous fin- ger movements-though not for less complex wrist movements before surgery-followed by a progressive increase toward the activation pattern of healthy controls, as functional gains in the upper extremity proceeded after surgical decompression. The reduced pinch-related activation and the normal amount of wrist extension-related activation in contralateral M1 and S1 before surgery suggest that the coordinated finger pinch task demands greater integrity of the corticospinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a larger study by Dong et al, 13 which included 8 patients with CSM and 6 healthy control volunteers, the authors quantitatively captured reduced activation in the contralateral M1, S1, and dorsal PMA for dexterous fin- ger movements-though not for less complex wrist movements before surgery-followed by a progressive increase toward the activation pattern of healthy controls, as functional gains in the upper extremity proceeded after surgical decompression. The reduced pinch-related activation and the normal amount of wrist extension-related activation in contralateral M1 and S1 before surgery suggest that the coordinated finger pinch task demands greater integrity of the corticospinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most commonly discussed mechanisms by which functional recovery occurs after decompression are synaptic changes and dendritic sprouting in the cortical and spinal cord neurons. 12,13 Rapid cortical and subcortical changes occurring after spinal cord injury (SCI) or myelitis have been demonstrated on functional imaging. 1 Cortical reorganization as well as improvement in corticospinal conduction happens during motor recovery after stroke, and this has been proved by studies using transcranial magnetic stimulation (TMS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Duffau et al 46 studied 77 patients with brain tumors without preoperative significant neurologic deficit and suggested, on the basis of their results with intraoperative cortical stimulation mapping, that recruitment of functionally compensatory brain regions adjacent to the tumor margins may account for the absence of preoperative deficits. In 4 patients with low-grade gliomas that infiltrated Broca area (Brodmann areas 44,45 ), they noted recruitment of the middle frontal gyrus and precentral gyrus, as well as the pars orbitalis of the inferior frontal gyrus as determined by speech arrest in these areas during intraoperative DECS. They also noted that eloquent structures may be present even within an area of brain tissue infiltrated by a low-grade glioma; they cite examples of 6 patients with gliomas infiltrating the insular cortex in which DECS of the insula resulted in speech arrest.…”
Section: The Phenomenon Of Postsurgical Plasticitymentioning
confidence: 99%
“…For example, Meunier et al 44 showed by using magnetoencephalography that resections of the somatosensory cortex have caused recruitment of perilesional sites adjacent to the resection cavity within the postcentral gyrus. In addition, Dong et al 45 studied the effects of decompression for cervical spondylotic myelopathy on primary somatosensory activation.…”
Section: The Phenomenon Of Postsurgical Plasticitymentioning
confidence: 99%